A new genus, Paraxantia gen. nov., with descriptions of four new species (Orthoptera: Tettigoniidae: Phaneropterinae) from China - Liu, Chun-Xiang; Kang, Le (Zootaxa, 2009)
Here we report a distinctive new genus Paraxantia gen. nov. (Orthoptera: Tettigoniidae: Phaneropterinae) from southern China. The new genus is distinguished from Xantia and other genera in the subfamily Phaneropterinae by the shape of fastigium verticis, the widened tegmen behind middle, and the complex sclerotized concealed genitalia. Description and important illustrations of four new species P. tibetensis sp. nov., P. hubeiensis sp. nov., P. parasinica sp. nov., and P. bicornis sp. nov. are presented. Xantia sinica Liu is transferred to Paraxantia with redescription and illustration. A key covering type species of Xantia Brunner von Wattenwyl and five species of Paraxantia gen. nov. is provided.